Prospective Memory Deficits Are Associated with Unemployment in Persons Living With HIV Infection - Woods, Steven Paul (2011)
OBJECTIVE: To determine whether deficits in prospective memory (i.e., “remembering to remember”) confer an increased risk of unemployment in individuals living with chronic HIV infection. METHODS: Fifty-nine Unemployed and 49 Employed individuals with HIV infection underwent comprehensive neuropsychological and medical evaluations, including measures of prospective memory. RESULTS: The Unemployed participants demonstrated significantly lower performance on time- and event-based prospective memory, which was primarily characterized by errors of omission. Importantly, prospective memory impairment was an independent predictor of unemployment when considered alongside other neurocognitive abilities, mood disturbance, and HIV disease severity. CONCLUSIONS: Prospective memory impairment is a salient predictor of unemployment in persons living with HIV infection and might be considered in screening for unemployment risk and developing vocational rehabilitation plans.